Post-Harvest Handling Holstein Friesian Milk at Susu Abadi Company in Tegal District - Krisjayanti Ataqwa; Melly Fera (Journal of Technology and Food Processing (JTFP), 2021)
Dairy cows are very important producers of animal protein. Milk as a source of nutrition in the form of animal protein is very beneficial. This study aims to determine the post-harvest process of Friesien Holsein's cow's milk in a susu abadi company in Tegal Regency. This research uses descriptive qualitative research. The sampling method for this research was purposive sampling method. Data collection methods used were observation, interviews, and documentation. The milking process in susu abadi companies is carried out twice a day, namely at 05.00 WIB and second at 15.00 WIB. After the milking process goes through the filtering stage, the resulting milk is filtered. a strainer made of cotton or a clean white cloth. In susu abadi company, large quantities of freshly milked fresh milk should be immediately cooled from 37⁰C to 4⁰C in order to maintain the milk temperature during 4⁰C storage. Volume of milk heated at a temperature of 62-65⁰C for 30-60 minutes. After the pasteurization process, the milk is put into a container and the milk is packed in a plastic bag with a volume of 1 liter. There are two products produced in susu abadi companies, namely fresh milk and pasteurized milk. Laboratory tests to determine the quality of milk produced by taking milk samples to be checked for quality